Yemen Country Profile 2010 - World Bank; International Finance Corporation (Washington, DC, 2017)
The enterprise surveys focus on the many factors that shape the business environment. These factors can be accommodating or constraining for firms and play an important role in whether a country will prosper or not. An accommodating business environment is one that encourages firms to operate efficiently. The enterprise surveys are conducted by the World Bank and its partners across all geographic regions and cover small, medium, and large companies. The surveys are administered to a representative sample of firms in the non-agricultural formal private economy. The enterprise surveys collect a wide array of qualitative and quantitative information through face to face interviews with firm managers and owners regarding the business environment in their countries and the productivity of their firms. The enterprise survey is useful for both policymakers and researchers. The surveys are repeated over time to track changes and benchmark the effects of reforms on firm's performance.